AM I COMPETENT ENOUGH? COMPETENCY ENABLERS AND BARRIERS OF EDUCATIONAL LEADERS IN THE PROVINCE OF CAPIZ - Andama, Jessa Mae Bartolo (President University, 2024)
The study aimed to assess the competency enablers and barriers of educational leaders in theProvince of Capiz for the 2023-2024 school year. Specifically, it sought to determine the extentof these enablers in terms of building connections, developing self and others, teaching andlearning, managing school operations, and strategic leadership. Additionally, the study aimedto identify the degree of competency barriers, including self-imposed, system-imposed, andculture-imposed barriers. It also examined whether there was a significant difference in theextent of enablers and barriers among respondents. The researcher utilized a mixed-methodapproach, combining quantitative data from a researcher-made questionnaire that was carriedout with a sample population of 224 from the total of 506 educational leaders with qualitativeinsights from in-depth interviews using the method of Colaizzi (1978) with five participantsfollowing Dworkin (2019).Proportionate random sampling was employed to determine thenumber of respondents per school. Statistical tools used were frequency count, percentage,mean, T-test, ANNOVA and Spearman rank correlation analysis. The study found moderatedegree of competency barriers among leaders, but widespread enablers. The study identifiedthree primary enablers: dialogic interdependence, curriculum-driven leadership, and strategicaptitude. These enablers emphasize the importance of collaborative networks, continuouslearning, and goal alignment for effective leadership. However, the research identified twoprimary obstacles to competency: ideological deflection and structural drawbacks. Structuraldrawbacks include hierarchical structures and diverse cultural backgrounds, while ideologicaldeflection lacks self-discipline and goal orientation. Practical recommendations includecustomized coaching and mentoring programs, systemic interventions, and leadershipdevelopment focused on cultural competency. Ethical considerations are ensured to ensureparticipant confidentiality and adherence to data privacy laws.